Denda Harta Terhadap Keterlambatan Perlunasan Hutang dalam Pendekatan Fiqh Muamalah - Aswita, Yessi (Ameena Journal, 2023)
Debt and credit within the framework of fiqh mu'amalah are not taboo subjects; the dynamics of indebtedness have been a recurring topic throughout history. Islam provides room for the practice of debt and credit, yet with systematic regulations. This transaction is known as a non-tijari (compensational contract) or tabarru' (gratuitous contract) transaction, in which the creditor does not expect any compensation from the debtor but assists with the intention of earning rewards from Allah SWT. Challenges arise when debtors fail to fulfill their promised repayment by the due date. This situation gives rise to issues, as the debtor's non-compliance infringes upon the rights of the creditor, which should be protected. Safeguarding the creditor's rights is an integral part of achieving the objectives of sharia. This study employs a literature review method aimed at exploring the viewpoints of both modern and classical scholars regarding appropriate sanctions for debtors who can pay off their debts but procrastinate. Consequently, the goals of justice and wisdom can be achieved in line with humanistic vertical principles.